Japanese Recruitment Practices in Times of Crisis - Firkola, Peter (Archives of Business Research, 2020)
This paper examines past recruitment practices to provide insight into how Japanese companies have adapted during times of crisis. A literature review combining company surveys and government-related statistical data was used. It was found that many large companies adapted recruitment processes in varying degrees to deal with the changing economic environment. These changes include varying the number of hires and diversifying hiring conditions. Although many Japanese companies adapt their recruitment processes, they seem resistant to change their overall recruitment strategy even during a crisis.